Recent advances in our understanding of neurodevelopmental outcomes in congenital heart disease. Issue 6 (December 2019) - White, Brian R.; Rogers, Lindsay S.; Kirschen, Matthew P.
Abstract : Purpose of review: Patients with congenital heart disease (CHD) suffer from a pattern of neurodevelopmental abnormalities including deficits in language and executive function. In this review, we summarize recent studies that examine these outcomes, their risk factors, possible biomarkers, and attempts to develop therapeutic interventions. Recent findings: The latest literature has highlighted the role of genetics in determining neurologic prognosis, as we have increased our understanding of potentially modifiable perioperative risk factors. The role of potentially neurotoxic medical therapies has become more salient. One recent focus has been how neurodevelopment affects quality of life and leads to a high prevalence of mental illness. Neuroimaging advances have provided new insights into the pathogenesis of deficits. Summary: Although many risk factors in CHD are not modifiable, there is promise for interventions to improve neurodevelopmental outcomes in patients with CHD. Biomarkers are needed to better understand the timing and prognosis of injury and to direct therapy. Research into psychosocial interventions is urgently needed to benefit the many survivors with CHD.